Blood flow restriction does not augment low force contractions taken to or near task failure - Buckner, S. L.; Jessee, M. B.; Dankel, S. J.; Mattocks, K. T.; Mouser, J. G.; Bell, Z. W.; Abe, T.; Bentley, J. P.; Loenneke, J. P. (European Journal of Sport Science, 2020)
Low-load exercise performed to or near task failure appears to result in similar skeletal muscle adaptations as low-load exercise with the addition of blood flow restriction (BFR). However, there may be a point where the training load becomes too low to stimulate an anabolic response without BFR. This study examined skeletal muscle adaptions to very low-load resistance exercise with and without BFR. Changes in muscle thickness (MTH), strength, and endurance were examined following 8-weeks of training with a traditional high-load [70% 1RM,(7000)], low-load [15% 1RM,(1500)], low-load with moderate BFR [15%1RM + 40%BFR(1540)], or low-load with greater BFR [15% 1RM + 80%BFR(1580)]. 1RM strength changes were greater in the 7000 condition [2.09 (95% CI = 1.35-2.83) kg] compared to all low-load conditions. For isometric and isokinetic strength, there were no changes. For endurance, there was a main effect for time [mean pre to post change = 7.9 (4.3-11.6) repetitions]. At the 50% site, the mean change in MTH in the 7000 condition [0.16 (0.10-0.22) cm] was greater than all low-load conditions. For the 60% site, the mean change in MTH [0.15 (0.08-0.22)] was greater than all low-load conditions. For the 70% site there was a main effect for time [mean pre to post change = 0.09 (0.05-0.14 cm]. All groups increased muscle size; however, this response was less in all very low training conditions compared to high-load training. 1RM strength increased in the 7000 condition only, with no other changes in strength observed.